2021
DOI: 10.3390/rel12050355
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Roles of Daily Spiritual Experiences, Self-Efficacy, and Gender in Shopping Addiction: A Moderated Mediation Model

Abstract: Although spirituality has been considered a protective factor against shopping addiction, the mechanisms involved in this relationship are still poorly recognized. The present study aims to test the association of daily spiritual experiences, self-efficacy, and gender with shopping addiction. The sample consisted of 430 young adults (275 women and 155 men), with a mean age of 20.44 (SD = 1.70). The Daily Spiritual Experiences Scale, the General Self-Efficacy Scale, and the Bergen Shopping Addiction Scale were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 135 publications
(202 reference statements)
1
10
0
3
Order By: Relevance
“…These results are consistent with those in very recent studies [36,38,63,64] that show a negative relationship between CB and self-efficacy. The lack of confidence by compulsive buyers in the ability to attain intrinsic goals of self-acceptance (to feel competent and autonomous, for instance) documented in some studies [53] is consistent with the results in this study.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those in very recent studies [36,38,63,64] that show a negative relationship between CB and self-efficacy. The lack of confidence by compulsive buyers in the ability to attain intrinsic goals of self-acceptance (to feel competent and autonomous, for instance) documented in some studies [53] is consistent with the results in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, it has been found that impulse buying is a strong predictor of shopping addiction (Charzy nska et al, 2021;Do ganKeskin & Günüç, 2017;Uzarska et al, 2021;Zhang et al, 2019). This implies that hedonic shopping motives also indirectly impact addiction through impulse buying.…”
Section: Mediating Role Of Hedonic Shopping Motivesmentioning
confidence: 99%
“…Additionally, Gong et al (2020) demonstrated that self‐efficacy positively mediates the association between the exterior design of a platform and impulse buying. The habit of impulse buying may gradually result in shopping addiction (Charzyńska et al, 2021; Zhang et al, 2019). Based on this finding, the present study also considered the positive mediating effect of self‐efficacy on shopping addiction through materialism (possessiveness, nongenerosity, and envy).…”
Section: Hypotheses Development and The Conceptual Modelmentioning
confidence: 99%
See 2 more Smart Citations